Recruitment of Herpes Simplex Virus Type 1 Immediate-Early Protein ICP0 to the Virus Particle - Maringer, Kevin (American Society for Microbiology (ASM), 2010)
Although the herpes simplex virus type 1 (HSV-1) tegument is comprised of a large number of viral and cellular proteins, how and where in the cell these proteins are recruited into the virus structure is poorly understood. We have shown previously that the immediate-early gene product ICP0 is packaged by a mechanism dependent on the major tegument protein VP22, while others have shown a requirement for ICP27. We now extend our studies to show that ICP0 packaging correlates directly with the ability of ICP0 to complex with VP22 in infected cells. ICP27 is not, however, present in this VP22-ICP0 complex but is packaged into the virion in a VP22- and ICP0-independent manner. Biochemical fractionation of virions indicated that ICP0 associates tightly with the virus capsid, but intranuclear capsids contained no detectable ICP0. The RING finger domain of ICP0 and the N terminus of VP22 were both shown to be essential but not sufficient for ICP0 packaging and complex formation. Strikingly, however, the N-terminal region of VP22, while unable to form a complex with ICP0, inhibited its translocation from the nucleus to the cytoplasm. PML degradation by ICP0 was efficient in cells infected with this VP22 mutant virus, confirming that ICP0 retains activity. Hence, we would suggest that VP22 is an important molecular partner of ICP0 that controls at least one of its activities: its assembly into the virion. Moreover, we propose that the pathway by which VP22 recruits ICP0 to the virion may begin in the nucleus prior to ICP0 translocation to its final site of assembly in the cytoplasm.